Application of a novel and green temperature-responsive deep eutectic solvent system to simultaneously extract and separate different polar active phytochemicals from Schisandra chinensis (Turcz.) Baill. (March 2023) - Yan, Xin-Yu; Cai, Zi-Hui; Zhao, Peng-Quan; Wang, Jian-Dong; Fu, Li-Na; Gu, Qi; Fu, Yu-Jie
Graphical abstract: Highlights: A temperature-responsive deep eutectic solvent (TRDES) system has been developed. TRDES was applied to obtain different polar phytochemicals from Schisandra chinensis . TRDES could be easily recycled and reused. The temperature switching mechanism was investigated and explored. The extraction mechanism of TRDES was demonstrated by density functional theory. Abstract: In the present study, a novel and green temperature-responsive deep eutectic solvent (TRDES) system was developed and applied for the simultaneous extraction and separation of different polar active phytochemicals from Schisandra chinensis (Turcz.) Baill. The TRDES, consisting of amino alcohols and phenolic compounds, was chosen as the switching medium, and an upper critical solution temperature (UCST) type switchable solvent was obtained by adding an inorganic salt solution. The switchable phase diagram was plotted based on the relationship between the phase change temperature, the concentration and the amount of sodium chloride solution. Under optimal parameters, the yields with TRDES for different polar active phytochemicals (lignanoids and polysaccharides) from the dried fruit of Schisandra chinensis (DFSC) were 1.62 ∼ 1.17-fold and 1.39-fold to those with conventional solvents. Also, the TRDES system was still effective on extraction of DFSC lignanoids and polysaccharides after four cycles of extraction. The separated polysaccharides and lignanoids both had strong antioxidant activities with IC50 values of 1.92 mg/ mL and 0.10 mg/ mL against 2, 2′-Azinobis(3-ethylbenzothiazoline-6-sulfonic acid)(ABTS), respectively. The extraction mechanism of TRDES was postulated by Density functional theory (DFT) calculations the hydrogen bonding in TRDES was the main factor to the higher extraction yield. This temperature-responsive deep eutectic solvent could be widely used for the efficient extraction and separation of multi-polar components. As a green and recyclable solvents, TRDES has great potential for the lower cost production from plants.